Storage ring mass spectrometry for nuclear structure and astrophysics research. (1st June 2016) - Zhang, Y H; Litvinov, Yu A; Uesaka, T; Xu, H S
Abstract: In the last two and a half decades ion storage rings have proven to be powerful tools for precision experiments with unstable nuclides in the realm of nuclear structure and astrophysics. There are presently three storage ring facilities in the world at which experiments with stored radioactive ions are possible. These are the ESR in GSI, Darmstadt/Germany, the CSRe in IMP, Lanzhou/China, and the R3 storage ring in RIKEN, Saitama/Japan. In this work, an introduction to the facilities is given. Selected characteristic experimental results and their impact in nuclear physics and astrophysics are presented. Planned technical developments and the envisioned future experiments are outlined.